The effects of C2 instability on cervical curvature changes and clinical outcomes after sub-axial cervical expansive door-open laminoplasty - Ma, Liang; Liu, Yuntao; Xi, Yanhai; Shi, Changgui; Meng, Xiangyu (Frontiers in Surgery, 2025)
ObjectiveTo investigate the impact of C2 vertebral instability on the sagittal parameters of the cervical spine and the clinical efficacy after cervical laminoplasty with unilateral open-door cervical expansive laminoplasty (EMOL).MethodsIn a retrospective analysis of 18 patients with cervical 2 vertebral instability from August 2017 to August 2021 in the second Affiliated Hospital of Naval Military Medical University and the Six Affiliated Hospital of Xinjiang Medical University treated with single open-door vertebroplasty (C3-6 or C3-7), 36 patients with stable cervical 2 cervical EMOL during the same period (control group). To evaluate the changes in sagittal parameters before and after surgery in the two groups, including C0-2 Cobb angle, C2-7 sagittal axis distance (sagittal vertical axis, SVA), C2-7 Cobb angle, T1 tilt angle (T1-Sl); The postoperative outcome was evaluated using the visual analogue score for neck and shoulder pain (visual analog scale, VAS) and the Japan Society Cervical Function Score (Japanese 0rthopaedic Association, JOA).ResultsCompared to preoperative values, both the observation group and the control group showed significant improvement in postoperative VAS scores and JOA scores. The JOA scores were 14.0 ± 1.6 and 13.1 ± 1.6, with improvement rates of 68.42% and 58.06%, respectively, compared to their respective preoperative scores. However, there was no significant difference between the two groups. The observation group had significantly greater cervical range of motion (ROM) before surgery compared to the control group (p < 0.05). At the last follow-up, the observation group showed a significant decrease in C2-7 Cobb angle from preoperative (8.2 ± 2.5)° to (5.1 ± 2.5)° (p < 0.05). Cervical ROM decreased from preoperative (39.8 ± 3.6)° to (31.6 ± 4.5)° (p < 0.05). C0-2 Cobb angle increased from preoperative (22.0 ± 3.7)° to (25.8 ± 3.1)° (p < 0.05). C2-7 SVA increased from preoperative (−19.6 ± 3.4)° to (−15.8 ± 3.7)° (p < 0.05). However, there was no significant change in T1 slope at the last follow-up (p > 0.05). The observation group showed a decrease in C2 vertebral displacement from preoperative (4.5 ± 0.9) mm to (3.3 ± 0.5) mm (p < 0.05), while the C2/3 angle showed no significant change compared to preoperative values (p > 0.05). In both groups, postoperative follow-up showed a significant increase in C0-2 Cobb angle and C2-7 SVA, a non-significant difference in T1 slope, and a significant decrease in C2-7 Cobb angle and cervical ROM compared to preoperative values. However, there were no significant differences between the two groups in the above-mentioned parameters (p > 0.05).ConclusionC2 vertebral instability does not affect the sagittal parameters and efficacy of cervical laminoplasty with EMOL. EMOL surgery for cervical myelopathy with C2 vertebral instability is effective and reliable, without exacerbating C2 vertebral instability. Furthermore, it maintains good sagittal balance of the cervical spine.